Postsurgical Perforation of the Esophagus Can Be Treated Using a Fully Covered Stent in Children. Issue 2 (February 2017) - Chauvet, Chantal; Bonnard, Arnaud; Mosca, Alexis; Bellaïche, Marc; Philippe-Chomette, Pascale; Viala, Jérôme
ABSTRACT: Objectives: Surgery and conservative treatment of esophageal or gastric perforations are both often associated with poor results and carry a high morbidity and mortality rate. The aim of the present study was to evaluate the effectiveness and safety of using fully covered self-expending metallic stents (SEMS) in children with upper digestive leaks. Methods: This retrospective study reviewed all children with esophageal or gastric perforation who were treated with placement of an SEMS from January 2011 to January 2015. Closure of the perforation was the primary outcome measured. Secondary outcomes were the duration of antibiotic therapy and parenteral nutrition, adverse events, and length of hospitalization. Results: A total of 19 SEMS were placed in 10 patients (median age: 5.5 years; 5 girls) treated for postanastomotic leaks of esophageal atresia (n = 3), esophagogastroplasty (n = 4), resection of esophageal duplication (n = 1) or perforation during Toupet surgical dismantling (n = 1), and gastric rupture after Nissen surgery (n = 1). The perforation closed in 9 out of 10 patients in a mean of 36 days after stenting (range: 13–158 days). All patients received antibiotic therapy for an average of 17.5 days (3–109 days) and parenteral nutrition for 49 days (17–266 days). During a median follow-up of 8.9 months, 4 out of 9 sealed perforations developed stenosis, which was efficiently treated by endoscopic dilations in 2 patients and surgical redo in 2 patients with dilation-resistant stenosis. Conclusions: Covered stents appear to be beneficial in closing esophageal perforations in children and can avoid the high morbidity of a surgical repair. Stenosis, however, occurred frequently after larger leakages.